A study on the perceptions of INPENS International College lecturers towards staff development programmes / Suzanah Selamat - Selamat, Suzanah (2005)
Staff development and training are gaining popularity as organizations become more aware of their importance. This is due to the changing nature of workplace in organisations which requires staff to have knowledge and skills in order to increase competence and performance. In addition, today's economic, social and technological changes also emphasize the value of staff development. Some of the benefits of staff development are that it encourages efficiency, innovation and quality in worker performance and productivity. In this context, higher education institutions should take steps in improving their staff development programmes so that their lecturers are prepared in developing students for the demand of the new job market. Furthermore, higher education institutions are facing increasing challenges to enhance their existing curriculum as well as putting adult learning theories into practice. However, many academic staff in higher education institutions do not have educational training. To improve their teaching skills, these staff should be encouraged to enrol in staff development programmes. This study examines the views and perceptions of lecturers towards staff development programmes. Sixty lecturers teaching in various subjects at INPENS International College participated in the study. Questionnaires were used as the instrument of the study. Results from the study indicated that generally lecturers at INPENS International College had very positive attitude towards staff development programmes and perceived these programmes as ways to enhance their pedagogical and student management skills. However, maybe due to lack of funding and planning, many of the participants were not satisfied with the current staff development programmes.